2020
DOI: 10.1590/0034-7167-2018-0360
|View full text |Cite
|
Sign up to set email alerts
|

Parental care for infants with feeding tube: psychosocial repercussions

Abstract: Objectives: to understand the psychosocial repercussions experienced by caregiving parents, resulting from care for the child with dysphagic cleft lip and palate. Methods: qualitative study, developed in a tertiary hospital in September 2016. The sample defined by theoretical saturation consisted of seven mothers. Data collection was performed by unstructured interview, being audio-recorded and fully transcribed. Symbolic Interactionism was used as theoretical framework, and Thematic Content Analysis as metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 18 publications
1
39
0
6
Order By: Relevance
“…Another research study that included informal caregivers of infants with orofacial cleft, dysphagia and who were fed by tube indicated that the mothers, for assuming the integral care of these children, either because they do not receive support or because they do not trust the provision of care provided by other people, felt overloaded and stressed 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research study that included informal caregivers of infants with orofacial cleft, dysphagia and who were fed by tube indicated that the mothers, for assuming the integral care of these children, either because they do not receive support or because they do not trust the provision of care provided by other people, felt overloaded and stressed 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In short, family-centered care models are needed to support the family unit in caring for a child with dysphagia and/or with eating difficulties. The parents and the informal caregivers must be included in the process and receive monitoring of their physical and mental well-being [12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In research, paediatric tube‐feeding tends to be addressed with reference to particular conditions or diseases (e.g. References 14–19), but some studies have examined tube‐feeding across more than one clinical domain 20,21 . Children who tube‐feed represent a heterogeneous group with multiple co‐morbidities 22 .…”
Section: Paediatric Tube‐feedingmentioning
confidence: 99%
“…Many families of children who tube‐feed say what matters to them is being connected with other families with children who tube feed 1,14 . Such connections are found by some families through social media groups, 14 but many remain disconnected from others sharing similar experiences.…”
Section: Principles: Involving Respecting and Connecting Familiesmentioning
confidence: 99%
See 1 more Smart Citation